Method for preparing two-dimensional material by multistage stripping of hexagonal phase layered material

Through the multi-stage peeling method of hexagonal phase layered material and erythritol, the problems of low yield and complex process of the existing two-dimensional material preparation methods are solved, and efficient and environmentally friendly two-dimensional nanomaterial preparation is achieved, which is suitable for industrial applications.

CN119637861APending Publication Date: 2025-03-18NANTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410056700.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Among the existing two-dimensional material preparation methods, the yield is low, the preparation process is complex, and the interlayer assisted peeling method has no significant efficiency on materials such as hexagonal boron nitride, making it difficult to achieve industrial application.

Method used

The multi-stage peeling method of hexagonal phase layered material and erythritol is adopted to achieve efficient preparation of two-dimensional materials through heating, melt mixing, pulverizing and expansion and liquid phase shearing.

Benefits of technology

It improves the yield of two-dimensional materials and realizes high-quality preparation of two-dimensional nanomaterials. It has simple process, environmental protection, low cost, and is suitable for industrial large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637861A_ABST
    Figure CN119637861A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a two-dimensional material by multi-stage stripping of a hexagonal phase layered material, which comprises the following steps: mixing the hexagonal phase layered material and erythritol according to a certain ratio, heating until polyol is molten, cooling at room temperature, recrystallizing the melt to obtain a recrystallized substance, and crushing and expanding the recrystallized substance by using an RM200 mortar grinder to obtain the two-dimensional material. The process is repeated for three times, so that crystal powder subjected to primary stripping and crushing can be obtained; crystal powder obtained after primary stripping and smashing is dissolved in 300 ml of water, mixed-phase fluid is formed and sheared through a continuous flow vertical plane type liquid-phase shearing device, during high-speed shearing, the stripping rotating speed is set to be 9500 rpm, high-speed shearing is conducted for 10 h through a liquid-phase microcavity, secondary stripping is achieved, and a mixed product can be obtained; centrifuging and washing the mixed product by using a washing centrifuge, and drying in a drying box at 80 DEG C for 12 hours to obtain a target product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a two-dimensional nano material, in particular to a method for preparing a two-dimensional material through multi-stage exfoliation of a hexagonal layered material. Background Art

[0002] Two-dimensional materials are nanomaterials with sheet-like morphology, ranging from hundreds of nanometers to tens of microns or even larger lateral dimensions, but with a thickness of only a single or a few atomic layers. Compared with bulk materials, the electrons in two-dimensional materials are confined in a two-dimensional structure. This unique structural feature gives them various unconventional physical and chemical properties, showing great application potential in many fields such as electronics / optoelectronics, catalysis, energy storage, solar energy, biomedicine, and environment.

[0003] In this context, efficiently obtaining high-quality two-dimensional materials has become a scientific research bottleneck that needs to be solved urgently. Similar to the preparation of conventional nanomaterials, the preparation of two-dimensional materials can also be divided into two paths: "from bottom to top" and "from top to bottom". Different preparation paths have their own advantages and applicable scenarios. For example, the gas phase synthesis method using the "bottom-to-top" path mainly emphasizes the growth of large-area two-dimensional materials. Chemical synthesis technology is mostly targeted at specific two-dimensional materials, such as the template method for the preparation of two-dimensional metal / metal alloy nanomaterials, two-dimensional metal organic framework materials (MOFs), layered bismuth oxysulfide compounds (Bi2O2Se), etc. The preparation process is complex and the equipment requirements are high;

[0004] The "top-down" strategy of preparing two-dimensional materials by exfoliating from bulk layered matrix materials has the potential for industrial application. The mainstream exfoliation techniques mainly include mechanical exfoliation and liquid phase exfoliation. Mechanical exfoliation can be traced back to the method of preparing graphene by Geim, Novoselov and others. High-quality precursor crystals and controllable exfoliation technology are the key to successful exfoliation, but the yield is low and it is mainly used in the study of material properties. Liquid phase exfoliation is a method of obtaining two-dimensional materials through shearing in solvents. At present, laboratory studies have confirmed the feasibility of intercalation-assisted liquid phase exfoliation in the preparation of two-dimensional or quasi-two-dimensional nanomaterials, and the yield is higher than mechanical exfoliation.

[0005] The technology has developed from the initial direct solvent exfoliation to intercalation-assisted exfoliation. Intercalation-assisted exfoliation mainly uses chemical / electrochemical methods to insert heterogeneous components such as small organic molecules or metal ions into the interlayers of layered materials to weaken the interlayer forces of layered materials. Studies have found that intercalation agents and exfoliation processes are crucial for obtaining thin nanosheets, and the shear effect is closely related to the interlayer interaction of the layered matrix material. For matrix materials with only a single van der Waals (VdW) effect between layers, such as graphite, the exfoliation efficiency of intercalation-assisted shear technology is relatively high. However, for matrix materials with interlayer van der Waals effects and lip-lip effects with localized ionic bonds, such as hexagonal boron nitride (h-BN), the effect is not very significant.

[0006] The invention patent with the Chinese patent publication number CN107364849B discloses a continuous flow vertical plane liquid phase shearing device, which can be used for liquid phase shearing processing of liquid materials;

[0007] Around the weakening of the interlayer interaction of layered materials, a large number of studies have reported various methods for interlayer insertion of heterogeneous components and their effects on stripping efficiency. Taking h-BN as an example, organic phases such as N,N-dimethylformamide (DMF) and polyvinylpyrrolidone (PVP) are used as solvents, and Li+ is introduced electrochemically. Alkaline NaClO and water generate OH- in situ, which are used as heterogeneous components for interlayer insertion. Then, combined with ultrasonic, ball milling and shearing treatments in liquid phase, these methods improve the efficiency of exfoliation to prepare two-dimensional nanosheets to a certain extent, but the yield is still low. The yield of preparing BN nanosheets (BNNSs) by ultrasonic exfoliation of h-BN in DMF is only 0.6%, and the highest NaClO-assisted exfoliation efficiency is only 21%. These results show that effective intercalation methods and exfoliation methods still need to be improved. For example, the insertion of intercalants mostly adopts the insertion method of liquid phase environment. Whether it is ultrasound, ball milling or shearing, the exfoliation method is mostly based on liquid phase shearing. This preparation path brings environmental pressure on the one hand, and the subsequent separation also brings difficulties to batch preparation.

[0008] Therefore, improving the insertion method and exfoliation path and increasing the yield of two-dimensional materials have become urgent issues to be solved in practical applications. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the defects of the above-mentioned technology and provide a method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials.

[0010] In order to solve the above technical problems, the technical solution provided by the present invention is a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material, comprising the following steps:

[0011] Step 1) Mix the hexagonal layered material and the intercalation agent in proportion, heat to 130 degrees, and keep for 10 minutes to melt and mix the hexagonal layered material and the intercalation agent to obtain a melt; cool at room temperature for 20 minutes to recrystallize the melt to obtain a recrystallized product, and then use an RM200 mortar grinder to crush and expand the recrystallized product to achieve primary exfoliation. This process is repeated three times to obtain a primary exfoliated crushed crystal powder;

[0012] Step 2) dissolving the primary exfoliated crushed crystal powder in 300 ml of water to form a mixed phase fluid, and shearing was performed using a continuous flow vertical planar liquid phase shearing device. During high-speed shearing, the exfoliation speed was set to 9500 rpm. After high-speed shearing in the liquid phase microcavity for 10 hours, secondary exfoliation was achieved to obtain a mixed product;

[0013] Step 3) The mixed product is centrifuged and washed using a washing centrifuge, and placed in a drying oven at 80° C. for 12 h to obtain the target product.

[0014] Furthermore, the hexagonal layered material is any one of hexagonal boron nitride and expanded graphite.

[0015] Furthermore, the intercalating agent is erythritol crystals.

[0016] Furthermore, the mass ratio of the hexagonal layered material to the intercalant is 1-2:5-10.

[0017] Furthermore, the RM200 mortar grinder is set with a rotation speed of 100 rpm and a time of 5 min.

[0018] Furthermore, the washing centrifuge is set at a rotation speed of 300 rpm and a time of 20 minutes.

[0019] Compared with the prior art, the present invention has the following advantages: the present invention uses hexagonal layered materials and erythritol as raw materials. Erythritol is a kind of sugar alcohol sweetener substance widely existing in plants and organisms in nature. After erythritol enters the interlayer and surface of the parent material, an appropriate form of mechanical force is applied to the system, and the layered material can be directly peeled off into a single layer or a few layers of two-dimensional nanomaterials; the erythritol solution obtained after centrifugation can be placed in a drying oven and recycled after drying. The preparation process does not involve chemical reactions, no toxic organic additives, etc., is green and environmentally friendly, low cost, simple process, high production efficiency, high concentration, cheap equipment, and easy to scale up. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a Raman spectrum diagram of Example 1 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material according to the present invention;

[0021] Figure 2 This is a Raman spectrum diagram of Example 2 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material according to the present invention;

[0022] Figure 3 This is a scanning electron microscope image of Example 1 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material according to the present invention;

[0023] in Figure 3 a is expanded graphite, Figure 3 b is the expanded graphite after primary exfoliation, Figure 3 c is the secondary exfoliated graphene.

[0024] Figure 4 This is a scanning electron microscope image of Example 2 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material according to the present invention;

[0025] in Figure 4 a is hexagonal boron nitride powder, Figure 4 b is the first-level exfoliation of hexagonal boron nitride. Figure 4 c is the secondary exfoliation of hexagonal boron nitride, Figure 4 d is the Tyndall plot of BNNSs dispersed in aqueous solution after standing for 24 hours. Figure 4 e is the typical morphology of the prepared BNNSs sheet at 8000 times magnification.

[0026] Figure 5 It is an XRD spectrum of Example 1 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material according to the present invention;

[0027] Figure 6 This is an XRD spectrum of Example 2 of a method for preparing a two-dimensional material by multi-stage exfoliation of a hexagonal layered material of the present invention. DETAILED DESCRIPTION

[0028] The following is a further detailed description of the method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to the present invention in conjunction with the embodiments.

[0029] Example 1

[0030] Step 1) 10g of erythritol crystals and 1g of expanded graphite were mixed, and the expanded graphite / erythritol crystal mixture was transformed into a solid / liquid phase at a high temperature of 130°C for 10 minutes, and then recrystallized after cooling at room temperature for 20 minutes, and then the expanded graphite / erythritol crystals were crushed using an RM200 mortar grinder to achieve primary exfoliation, with a speed of 100 rpm and a time of 5 minutes. This process was repeated 3 times;

[0031] Step 2) dissolving the primary exfoliated crushed expanded graphite / erythritol crystal powder in 300 ml of water to form a mixed phase fluid, and shearing was performed using a continuous flow vertical planar liquid phase shearing device. During high-speed shearing, the exfoliation speed was set to 9500 rpm, and the liquid phase microcavity high-speed shearing was performed for 2 hours to achieve secondary exfoliation, thereby obtaining a mixed product;

[0032] Step 3) The mixed product is centrifuged and washed in a washing centrifuge, wherein the washing centrifuge is set to a speed of 300 rpm for 20 min and placed in a drying oven at 80° C. for 12 h to obtain 0.9 g of powder with a yield of up to 90%.

[0033] The product of Example 1 was analyzed by scanning electron microscopy, XRD spectrum, and Raman spectrum. It can be seen from the scanning electron microscopy that the expanded graphite ( Figure 3 a) Expanded graphite after primary peeling ( Figure 3 b) Secondary exfoliation of graphene ( Figure 3 c) SEM morphology shows that the graphene after secondary exfoliation has a loose structure, showing curled, transparent and wrinkled shapes;

[0034] from Figure 1 It can be seen that the half-peak width of the 2D peak of graphene is gradually increased compared with that of EG and shifts to a higher wave number (blue shift). The peak intensities of the characteristic peaks 2D peak and G peak of graphene and EG are compared (I 2D / I G ) analysis, graphene (I 2D / I G =0.628)>EG(I 2D / I G =0.0.57), the larger the ratio, the fewer graphene layers there are. This indicates that graphene nanosheets are obtained after secondary exfoliation. Raman spectroscopy test wavelength 532nm, test range 100-3200cm -1 , powder sample 10mg.

[0035] from Figure 5 It can be seen that the XRD peaks of expanded graphite, primary exfoliated graphite, and secondary exfoliated graphene appear at 26.46°, 26.42°, and 26.28°, respectively, and the XRD peaks are slightly shifted to smaller angles.

[0036] Example 2

[0037] Step 1) 5 g of erythritol crystals and 1 g of hexagonal boron nitride powder were mixed, and the hexagonal boron nitride / erythritol crystal mixture was transformed into a solid / liquid phase at a high temperature of 130° C. for 10 min, and then recrystallized after cooling at room temperature for 10 min, and then the hexagonal boron nitride / erythritol crystals were crushed using an RM200 mortar grinder to achieve primary exfoliation, with a speed of 100 rpm and a time of 5 min. This process was repeated 3 times.

[0038] Step 2) The primary exfoliated and crushed hexagonal boron nitride / erythritol crystal powder is dissolved in 300 ml of water to form a mixed phase fluid, and sheared using a continuous flow vertical planar liquid phase shearing device. During high-speed shearing, the exfoliation speed is set to 9500 rpm. After high-speed shearing in the liquid phase microcavity for 10 hours, secondary exfoliation is achieved to obtain a mixed product.

[0039] Step 3) The mixed product is centrifuged and washed in a washing centrifuge, wherein the washing centrifuge is set to a speed of 300 rpm for 20 min and placed in a drying oven at 80° C. for 12 h to obtain 0.3 g of solid BNNSs powder with a yield of up to 30%.

[0040] The product of Example 1 was analyzed by scanning electron microscopy, XRD spectrum, and Raman spectrum. It can be seen from the scanning electron microscopy that the hexagonal boron nitride powder ( Figure 4 a) Primary peeling of hexagonal boron nitride ( Figure 4 b) and secondary exfoliation of hexagonal boron nitride ( Figure 4 c) Typical SEM morphology at the same magnification, where Figure 4 a shows that the original h-BN has a lateral size of about 30 μm and a side thickness of micrometers. After the first peeling, the h-BN is partially thinned and the edge is curled ( Figure 4 b), after secondary peeling, the h-BN presents a quasi-two-dimensional flake morphology ( Figure 4 c) Further characterization of BNNSs is shown in Figure 4 d and Figure 4 e in. Figure 4 d is the Tyndall diagram of BNNSs dispersed in aqueous solution and left to stand for 24 hours. The Tyndall light column is stable and uniform, showing the stability of BNNSs in aqueous solution; Figure 4 e is the typical morphology of the prepared BNNSs sheet at 8000 times. The BNNSs sheet is very thin and wrinkled, with a thickness far less than the micrometer level;

[0041] from Figure 2 It can be seen that at a wavelength of 1366cm -1 Peaks can be observed, indicating that the sample crystal structure was not destroyed during the exfoliation process;

[0042] from Figure 6It can be seen that the peaks of the XRD spectra of the primary exfoliated h-BN and the secondary exfoliated BNNSs are compared with the standard PDF card of h-BN. The diffraction angles of 25.92° and 54.44° correspond to the (002) and (004) crystal planes of h-BN, respectively, indicating that the hexagonal crystal system of the primary exfoliated h-BN and the secondary exfoliated BNNSs is intact.

[0043] The working principle of the present invention is as follows: a layered matrix material and a suitable polyol in a certain ratio are mixed and heated until the polyol is melted, and then stirred and mixed in a molten state. The layered material expands due to the heat, and the polyol enters the interlayers and surface of the matrix material. With the help of the large π bonds between the organic molecules and the layered material layers, the two produce a CH-π effect at the interface, and the matrix material in the interface provides a nucleation site for the polyol to crystallize naturally when cooled, and a polyol mixed polycrystal doped with the layered matrix material is formed.

[0044] According to crystal theory, crystals are prone to brittle fracture along cleavage planes under external forces, and fractures are prone to occur in stress concentration areas. For polyol melt mixed polycrystals, the interface between the surface of the matrix material and the polyol, and the interface between the matrix material layers and the polyol are stress concentration areas, and the interlayer effect of the layered material is much weaker than the intralayer effect. During the ball milling or crushing process, fractures are prone to occur along the layer direction and peeling off into thinner powders, achieving primary peeling of the layered matrix material;

[0045] The powder after primary peeling is dissolved in an appropriate amount of water to form a suspension with a certain viscosity. The suspension is introduced into a shear microcavity composed of parallel surfaces. The suspension is driven by a high-speed rotating disk and a Couette shear flow field is formed between the moving disk and the static disk. The shear stress in the flow field is related to the velocity gradient and the viscosity coefficient. For layered matrix materials, the shear stress can be expressed as τ = μdv / dx, where μ is the viscosity coefficient and dv / dx is the velocity gradient of the upper and lower interfaces of the matrix. For a material with a certain lateral size, if its sheet area is A, the shear force acting on it is F = Aτ. When the shear force is greater than the interlayer force, the layers slide relative to each other and separate.

[0046] The polyol dissolved in water can adjust the viscosity and prevent the re-overlapping of the exfoliated layers. The suspension that has been sheared for a long time is filtered or slowly centrifuged to separate the exfoliated layer matrix and the liquid phase solvent. The liquid phase solvent can be reused after freeze drying and recrystallization. The exfoliated layer matrix is ​​washed with deionized water for many times, centrifuged and dried.

[0047] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.

Claims

1. A method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials, characterized in that: The following steps are involved: Step 1) Mix the hexagonal layered material and the intercalation agent in proportion, heat to 130 degrees, and keep for 10 minutes to melt and mix the hexagonal layered material and the intercalation agent to obtain a melt; cool at room temperature for 20 minutes to recrystallize the melt to obtain a recrystallized product, and then use an RM200 mortar grinder to crush and expand the recrystallized product to achieve primary exfoliation. This process is repeated three times to obtain a primary exfoliated crushed crystal powder; Step 2) dissolving the primary exfoliated crushed crystal powder in 300 ml of water to form a mixed phase fluid, and shearing was performed using a continuous flow vertical planar liquid phase shearing device. During high-speed shearing, the exfoliation speed was set to 9500 rpm. After high-speed shearing in the liquid phase microcavity for 10 hours, secondary exfoliation was achieved to obtain a mixed product; Step 3) The mixed product is centrifuged and washed using a washing centrifuge, and placed in a drying oven at 80° C. for 12 h to obtain the target product.

2. The method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to claim 1, characterized in that: The hexagonal layered material is any one of hexagonal boron nitride and expanded graphite.

3. The method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to claim 1, characterized in that: The intercalating agent is erythritol crystals.

4. The method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to claim 1, characterized in that: The mass ratio of the hexagonal layered material to the intercalant is 1-2:5-10.

5. The method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to claim 1, characterized in that: The RM200 mortar grinder was set to a rotation speed of 100 rpm and a time of 5 min.

6. The method for preparing two-dimensional materials by multi-stage exfoliation of hexagonal layered materials according to claim 1, characterized in that: The washing centrifuge was set to rotate at 300 rpm for 20 min.

Citation Information

Patent Citations

  • Continuous flow vertical planar liquid phase shearing device

    CN107364849B

  • High-phase-change thermoset phase change material and preparation method thereof

    CN102827584A

  • Preparation method of phase-change composite material with high heat conductivity and high density

    CN104774594A

  • Apparatus and method for preparing two-dimensional material by liquid-phase dissection method

    CN107217305A

  • Preparation of molded expanded graphite-based erythritol medium-temperature composite phase change heat storage material

    CN107603571A